1997
DOI: 10.1046/j.1365-3156.1997.d01-297.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Trypanosoma rangeli against infections with a highly virulent strain of Trypanosoma cruzi

Abstract: We investigated the protective effect of Trypanosoma rangeli against infection with Trypanosoma cruzi in animal models of various ages and with different doses of inoculum. The age of the mice and the dose of parasites determined the course of the infection. When T. cruzi was inoculated into mice after challenge with T. rangeli, parasitaemia was more controlled, mortality decreased and histopathology showed lower inflammatory infiltration and pseudocysts. This study proposes a new murine model of the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Conversely, Scorza et al (1986), ZunÄ iga et al (1997b) reported the presence of intracellular amastigotes in mice experimentally infected with the Perro-82 and C23 T. rangeli strains. Reports of longterm detection of T. rangeli in chronically infected animals show that this parasite is able to survive for a long period in the vertebrate host (D'Alessandro and Saravia 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Scorza et al (1986), ZunÄ iga et al (1997b) reported the presence of intracellular amastigotes in mice experimentally infected with the Perro-82 and C23 T. rangeli strains. Reports of longterm detection of T. rangeli in chronically infected animals show that this parasite is able to survive for a long period in the vertebrate host (D'Alessandro and Saravia 1992).…”
Section: Discussionmentioning
confidence: 99%
“…For endemic regions in Panama, T. rangeli is more frequently found in human blood than T. cruzi 23 . In this sense, recent data have shown that complete or partial immunity against T. cruzi can be obtained in animal models previously immunized with low virulent T. cruzi strains 5,9 or with T. rangeli 1,29 . The fact that more than one T. cruzi strain 10,16 and even more than one Trypanosoma species 6,23 can be transmitted by R. pallescens in Panama makes this possibility feasible.…”
Section: Discussionmentioning
confidence: 99%
“…34 Similarly, immunization with live T. rangeli, a related parasite species non-pathogenic in humans, can also provide some cross-reactive immunity and partial protection, possibly due to homologous antigens. [35][36][37] However, these approaches raise the issues commonly associated with live vaccines, i.e., safety and the challenges associated with their large-scale production and distribution. Nonetheless, there is a renewed interest in a live attenuated vaccine approach and recent studies have described the generation of T. cruzi mutants for specific genes such as LYT1 or ECH1 and 2, which can provide good protection against infection in mice, including through oral administration.…”
Section: Current Status Of Vaccine Researchmentioning
confidence: 99%